Boavyav
4 год назад
Запишите в виде квадрата. 9(u-v)^2+(u+v)^2-6(u-v)(u+v)
ОТВЕТЫ
Йорданка
Oct 6, 2020
6u^2 + 4v^2
Объяснение:
Формула (а-в)^2 = а^2-2*а*в + в^2
1.)Подставляем -
9(u-v)^2 = 9(u^2-2uv-u^2),
2.) Далее умножаем на 9 -
9u^2 - 9*2uv + 9u^2
3.) Формула (а+в)^2 = а^2 + 2ав + в^2
подставляем
u^2 + 2 uv + v^2
4.) Формула (а+в)(а-в) = а^2 - в^2
подставляем
6( u^2 - v^2)
5.) Умножаем на (-6) -
(-6) * u^2 - (-6) * v^2 = -6u^2 + 6v^2
6.) Совмещаем :
9u^2 - 2uv + v^2 + u^2 + 2uv + v^2 - 6u^2 + 6 v^2
2uvи -2 uv зачёркиваем
9u^2 + u^2 - 6u^2 + 6 v^2 + v^2 + v^2
9u^2 + u^2 - 6u^2 = 4 u^2
6v^2 + v^2 + v^2 = 8 v^2
Складываем и получаем: 6u^2 + 4v^2
417
Смежные вопросы: